2016
DOI: 10.1515/acgeo-2016-0090
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Strength, Resistivity and Thermal Parameters of Clay after High Temperature Treatment

Abstract: This paper reports the variations of strength, resistivity and thermal parameters of clay after high-temperature heating. Experiments were carried out to test the physical properties of clay heated at temperatures ranging from room temperature to 800°C in a furnace. The experiment results show that below 400°C the uniaxial compressive strength and resistivity change very little. However, above 400°C, both increase rapidly. At a temperature under 400°C, the thermal conductivity and specific heat capacity decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Figure 2(b) presents the permeability of granite which increased sharply around 500°C. is observation was in accordance with the evolution of total porosity at this temperature [80][81][82][83][84][85].…”
Section: Porosity and Permeability Evolution Depending On Thesupporting
confidence: 89%
See 3 more Smart Citations
“…Figure 2(b) presents the permeability of granite which increased sharply around 500°C. is observation was in accordance with the evolution of total porosity at this temperature [80][81][82][83][84][85].…”
Section: Porosity and Permeability Evolution Depending On Thesupporting
confidence: 89%
“…At 898°C, the author of [43] showed that the decarbonisation was completed and caused a breakdown of the aggregates. (6) Clay minerals and phyllo silicate were more sensitive to heat and showed severe transformations at high temperature [46]. In this category of minerals, we found the alteration of silicates minerals (feldspars, for example) such as kaolinite, sericite, and illite.…”
Section: Influence Of Temperature On Mineralogical Compositionmentioning
confidence: 81%
See 2 more Smart Citations
“…The main temperature‐dependent properties required for thermal simulations are thermal conductivity, specific heat capacity, and bulk density. Several researches have investigated the thermophysical properties of various soils, clay, and limestone 9,10 . However, these materials are different from the plasters used in buildings.…”
Section: Introductionmentioning
confidence: 99%